2017
DOI: 10.1037/sah0000060
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and sickle cell pain: The moderating role of internalized stigma.

Abstract: Recent studies describe the clinical implications of sickle cell disease (SCD) stigma. However, little is known about its link to depressive symptoms or its relative influence on the association between depressive symptoms and SCD pain. We examined whether internalized stigma about SCD moderated the relation between depressive symptoms and pain among 69 adults attending a SCD clinic who reported pain episodes and healthcare use over the past three months. Unadjusted bivariate analyses showed a marginal associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
2
15
0
1
Order By: Relevance
“…Of the 27 studies reviewed, five used scales adapted for stigma of SCD (Bediako et al, 2014; Blake et al, 2017; Holloway, McGill, & Bediako, 2016; Jenerette, Brewer, Crandell, & I. Ataga, 2012; Jenerette, Brewer, Edwards, Mishel, & Gil, 2014). The remainder did not include a scale, adapted a scale about stigma or a stigma-related concept fromanother population, or interviewed participants about stigma and stigma-related concepts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 27 studies reviewed, five used scales adapted for stigma of SCD (Bediako et al, 2014; Blake et al, 2017; Holloway, McGill, & Bediako, 2016; Jenerette, Brewer, Crandell, & I. Ataga, 2012; Jenerette, Brewer, Edwards, Mishel, & Gil, 2014). The remainder did not include a scale, adapted a scale about stigma or a stigma-related concept fromanother population, or interviewed participants about stigma and stigma-related concepts.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of SCD literature focuses on perceived stigma in SCD and its effects on patient-provider relationships, care-seeking behaviors, and the mental and physical wellbeing of individuals with SCD. However, the impact of internalized stigma also needs to be assessed, as Holloway et al (2016) found a positive relationship between internalized stigma and depressive symptoms. Additionally, SCD stigma often goes unrecognized, unaddressed, and is not measured in studies assessing psychological wellbeing in SCD, despite all of the literature confirming that stigma is associated with poor psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, patients in the former group would be less likely to utilize health care services when in pain, while those in the latter group would be more likely to do so. Conversely, individuals with a stronger racial self-concept may be more sensitive to perceived discrimination and stigmatization (Haywood et al, 2014; Holloway et al, 2016) and may be hesitant—even when in severe pain—to engage with the traditional health care system in order to avoid being treated unfairly. This might explain why individuals high in racial centrality report fewer emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated pain severity by asking participants to rate the global intensity of these episodes on a scale ranging from 0 ( no pain at all ) to 10 ( pain as bad as it can be ). These indicators have been used for more than two decades in SCD research with adults and are highly correlated with objective clinical indicators of disease severity (Holloway, McGill, & Bediako, 2016). …”
Section: Methodsmentioning
confidence: 99%